Evaluation of micronucleus frequency in oral exfoliated buccal mucosa cells of smokers and tobacco chewers: a comparative study - Agrawal, Vandana; Dubey, Ishan; Mishra, K. B. (International Journal of Research in Medical Sciences, 2017)
Background: Oral cancer is one of the tenth most common cancers in the world and constitutes the third most important group of malignancies in India. Majority of these cancers are diagnosed at an advanced stage resulting in poor prognosis and survival rates among patients. Hence early diagnosis of oral cancers seems to be the need of the hour. Analysis of exfoliated buccal cell micronuclei (MN) is a sensitive method of monitoring genetic damage. The present study aims to compare the frequency of micronucleus in tobacco chewers and smokers and thus evaluate the genotoxic potential of these habits. Methods: The study was conducted on 60 subjects, divided into 3 groups each of 20 subjects. Group 1: with history of chewing tobacco, group 2: with history of chewing tobacco and smoking, group 3: healthy subjects without any habits as controls. Oral exfoliated cells were obtained from buccal mucosa of the subjects, 2 slides were prepared from each subject stained with Giemsa and H&E stain respectively. Atleast 1000 cells were examined for each subject and micronuclei frequency was scored according to criteria of Tolbert et al. Results: The mean number of micronuclei was 18.5±9.5 in tobacco chewers, 19.1±9.2 in chewers with smoking habit and 8.2±5.6 in controls. Bonferroni multiple comparisons amongst these three groups showed the mean difference of micronuclei to be highly significant when chewers and chewers with smoking habit were compared to controls. Similarly based on the duration of addiction, a highly significant difference was noted in no. of micronucleated cells in subjects addicted to tobacco for more than 15 years. Conclusions: Tobacco can cause and increase the rate of nuclear anomalies in both smoking and smokeless forms. Thus oral mucosal micronuclei frequency can be used as a marker of epithelial carcinogenic progression.